STRATEGI PENANGANAN ANAK TIDAK SEKOLAH (P-ATS) DI KABUPATEN MAGELANG: MENINGKATKAN AKSES DAN KESADARAN PENDIDIKAN - S, Nurjto A; Supardal, Supardal (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Education is a fundamental right of every child and the key to individual and societal development. However, in Magelang Regency, around 1,200 school-aged children were not enrolled in formal schools in 2023. Many factors such as social stigma, limited access, and poverty contribute to this issue. Children from low-income families tend not to continue their education due to costs and the distance to school. This research applies a subjective approach with a case study to understand the reality of school dropouts in Magelang Regency. Five informants were randomly selected: two teachers, two parents, one student, and one representative from an educational institution. The data was obtained through semi-structured interviews and analyzed thematically. This research also involves a Systematic Literature Review of ten articles to support the findings. The results of interviews with five informants—teachers, parents, students, and representatives from the Education Office—show that some of the main reasons why children in Magelang Regency do not attend school are family financial issues, lack of desire to learn, and limited access to schools. Although scholarships and alternative learning programs have been used to help children return to school, there are still issues, particularly related to parental social support. The research conclusion shows that the issue of children are out of school (ATS) in Magelang Regency is influenced by limited access to education and a lack of motivation. The difficult economic conditions of the family force children to work, hindering their education. Although there are efforts from the Education Office to provide assistance and alternative programs, synergy between the government, schools, and the society community is essential for improving the access and awareness of education. ABSTRAKPendidikan adalah hak dasar setiap anak dan kunci perkembangan individu serta masyarakat. Namun, di Kabupaten Magelang, sekitar 7.897 anak usia sekolah tidak terdaftar di sekolah formal pada 2023. Faktor-faktor seperti stigma sosial, akses terbatas, dan kemiskinan berkontribusi pada masalah ini. Anak-anak dari keluarga kurang mampu cenderung tidak melanjutkan pendidikan akibat biaya dan jarak sekolah yang jauh. Penelitian ini menerapkan pendekatan subjektif dengan model telaah kasus untuk memahami realita anak putus sekolah di Kabupaten Magelang. Lima informan dipilih secara acak: dua guru, dua wali murid, satu murid, dan satu perwakilan lembaga pendidikan. Data diperoleh melalui tanya jawab semi-terstruktur dan dikaji secara tematis. Riset ini juga melibatkan Systematic Literature Review dari sepuluh artikel untuk mendukung temuan. Hasil wawancara dengan lima informan; guru, wali murid, siswa, dan perwakilan dari Dinas Pendidikan dan Kebudayaan menunjukkan bahwa beberapa alasan utama mengapa anak-anak di Kabupaten Magelang tidak sekolah adalah masalah keuangan keluarga, kurangnya keinginan untuk belajar, dan akses terbatas ke sekolah. Meskipun beasiswa dan program pembelajaran alternatif telah digunakan untuk membantu anak-anak kembali bersekolah, masih ada masalah, terutama terkait dukungan sosial dari orang tua. Kesimpulan penelitian menunjukkan bahwa masalah anak tidak sekolah (ATS) di Kabupaten Magelang dipengaruhi oleh akses terbatas ke pendidikan dan kurangnya motivasi. Kondisi ekonomi keluarga yang sulit memaksa anak-anak untuk bekerja, menghambat pendidikan mereka. Meskipun ada upaya dari Dinas Pendidikan dan Kebudayaan untuk memberikan bantuan dan program alternatif, kolaborasi antara pemerintah, sekolah, dan masyarakat sangat diperlukan untuk meningkatkan akses dan kesadaran pendidikan.